2018
DOI: 10.1007/s00330-018-5349-7
|View full text |Cite
|
Sign up to set email alerts
|

Solitary fibrous tumour of the spine: imaging features of a commonly misdiagnosed entity

Abstract: • Spinal solitary fibrous tumours are extremely rare. • SFTs should be showed the differential of masses developing though the foramen. • Combing imaging with pathology and immunochemistry assesses the diagnosis and establish nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In our study, SFTs demonstrated well-defined homogeneous masses with or without bony destruction on CT, and calcifications were rarely observed, which is consistent with previous studies 5,8,10 . However, the characteristics on MRI were partly different from those reported in previous studies 8,9,12 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, SFTs demonstrated well-defined homogeneous masses with or without bony destruction on CT, and calcifications were rarely observed, which is consistent with previous studies 5,8,10 . However, the characteristics on MRI were partly different from those reported in previous studies 8,9,12 .…”
Section: Discussionsupporting
confidence: 90%
“…5 To the best of our knowledge, only a few cases of spinal SFTs have been reported in the literature. [5][6][7][8][9][10][11][12] Given the rarity of this disease, its imaging characteristics remain unclear.…”
mentioning
confidence: 99%
“…12 SFT is considered to be rare as a cause of dumbbell tumor: only 16 cases were reported before, and 4 of 16 were malignant, to our knowledge. 8,9,13,14 As for our case, we consider it is quite difficult to differentiate MSFT from other more common dumbbellshaped tumor such as schwannoma by clinical presentation. And imaging findings might be of little help.…”
Section: Discussionmentioning
confidence: 82%
“…12 SFT is considered to be rare as a cause of dumbbell tumor: only 16 cases were reported before, and 4 of 16 were malignant, to our knowledge. 8,9,13,14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation